Petroleum Degradation in Soil by Thermophilic Bacteria with Biopile Reactor - Nugroho, Astri; Effendi, Edison; Karonta, Yulius (UI Scholars Hub, 2010)
Crude oil degradation has been carried out using biopile reactor in total petroleum hydrocarbon (TPH) concentration of 5%, 10% and 15%. The thermophilic microorganisms used from isolation result and identification are Aeromonas salmonicida, Bacillus pantothenticus, and Stenotrophomonas maltophilia. The biodegradation of biopile reactor is done by various concentrations of TPH, total plate count (TPC), and volatile suspended solid (VSS) per day for 30 days. The biodegradation of kinetic parameter calculated consists of μ, μm, Y, Yt, Yobs, Kd, Ks from TPH concentration decision, and TPC and VSS in every microorganism with t (observation time) of 0 hour to 168 hours. The crude oil separation efficiency in a biople reactor shows that the largest separation occurs in a starting TPH concentration of 15%, which becomes 61.8% later on, followed by a starting TPH concentration of 10% and 5%, which is as much as 61% and 48.4%.